2022
DOI: 10.3390/mi13122196
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nonlinear Convection–Radiation in Chemically Reactive Oldroyd-B Nanoliquid Configured by a Stretching Surface with Robin Conditions: Applications in Nano-Coating Manufacturing

Abstract: Motivated by emerging high-temperature manufacturing processes deploying nano-polymeric coatings, the present study investigates nonlinear thermally radiative Oldroyd-B viscoelastic nanoliquid stagnant-point flow from a heated vertical stretching permeable surface. Robin (mixed derivative) conditions were utilized in order to better represent coating fabrication conditions. The nanoliquid analysis was based on Buongiorno’s two-component model, which features Brownian movement and thermophoretic attributes. Non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Ramzan et al 7 looked into the mixed convective flow Casson fluid in presence of gyrotactic microbes between two concentric cylinders. Nasir et al 8 analysed non-linear convective -radiative flow of Oldroyd B non-Newtonian fluid when subjected Robin’s boundary condition. They have concluded that increasing relaxation parameter diminishes velocity profile.…”
Section: Introductionmentioning
confidence: 99%
“…Ramzan et al 7 looked into the mixed convective flow Casson fluid in presence of gyrotactic microbes between two concentric cylinders. Nasir et al 8 analysed non-linear convective -radiative flow of Oldroyd B non-Newtonian fluid when subjected Robin’s boundary condition. They have concluded that increasing relaxation parameter diminishes velocity profile.…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al [13] provided a review of fabrication methods and potential applications concerning the anisotropic wetting of surfaces. Nasir et al [14] conducted a study on the flow effects of Oldroyd-B fluids on stretching surfaces, considering chemical reactions occurring on the surfaces. Khan et al [15] analyzed surface extrusion effects for viscoelastic fluids over oscillatory surfaces, with a focus on porosity effects.…”
Section: Introductionmentioning
confidence: 99%
“…They stated that the heat conduc�vity is significantly increased (by more than 100%) as a result of the magne�c field these nanopar�cles produce. Further studies in this direc�on are men�oned in references [36][37][38][39][40][41][42].…”
Section: Introduc�onmentioning
confidence: 99%